The expression of heat shock protein 70 gene with organic selenium supplementation and its effetc on productivity of broilers in tropical environment - Amizar, R.; Suharti, S.; Jakaria, J.; Mutia, R. (Diponegoro University, 2017)
The purpose of this experiment is to study the effect of organic selenium (Se) supplementation on the expression of heat shock protein 70 gene (HSP70), glutathione peroxidase (GSH-Px) enzyme activity, malondialdehyde (MDA) and productivity of broilers in tropical environment. Three kinds of environmental pens were designed in this experiment: comfortable environment pens with temperature of air conditioner adjusted at 22oC (R0), tropical environment pens (±30oC ) without organic Se (R1), and tropical environment pens supplemented with 0.30 ppm organic Se (R2). One hundred and twenty broiler chickens (unisex) were used in this study. There were 40 chicks per pen for each treatment. The experimental design was completely randomized with four replications for each treatment. The data were statistically analyzed using the general linear model of SAS program. Results showed that R0 and R2 groups had significantly increased (P<0.05) feed intake, body weight, body weight gain, and decreased feed conversion ratio compared to R1 groups. Meanwhile, the expression of HSP70, GSH-Px enzyme activity and MDA of R2 groups and R0 groups were significantly lower (P<0.05) than that of R1 groups. It was concluded that the broilers given 0.30 ppm organic Se in tropical environment had similar productivity and expression of HSP 70 with broilers kept in comfortable environment.